Gut Microbiota Is Not Essential for Survival and Development in Blattella germanica, but Affects Uric Acid Storage - Domínguez-Santos, Rebeca; Baixeras, Joaquín; Moya, Andrés; Latorre, Amparo; Gil, Rosario; García-Ferris, Carlos (Life (Basel, Switzerland), 2024)
Cockroaches harbor two coexisting symbiotic systems: the obligate endosymbiont Blattabacterium cuenotii, and a complex gut microbiota. Blattabacterium is the only bacterium present in the eggs, as the gut microbiota is acquired by horizontal transmission after hatching, mostly through coprophagy. Blattella germanica, a cosmopolitan omnivorous cockroach living in intimate association with humans, is an appropriate model system for studying whether the gut microbiota is essential for the cockroach’s survival, development, or welfare. We obtained a germ-free cockroach population (i.e., containing normal amounts of the endosymbiont, but free of microbes on the insects’ surface and digestive tract). Non-significant differences with the controls were detected in most fitness parameters analyzed, except for a slight shortening in the hatching time of the second generation and a reduction in female weight at 10 days after adult ecdysis. The latter is accompanied by a decrease in uric acid reserves. This starvation-like phenotype of germ-free B. germanica suggests that the microbiota is not essential in this species for survival and development throughout its complete life cycle, but it could participate in complementation of host nutrition by helping with food digestion and nutrient absorption.